Messenger of the Lord - Douglass, Herbert E.; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 1998)
Is the most comprehensive treatment ever produced of Ellen White's prophetic ministry. It is the definitive work on how the prophetic gift functioned in her life and ministry.
Keywords: Adult Nonfiction